2017
DOI: 10.3168/jds.2016-11951
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between direct and indirect methods for exploiting Fourier transform spectral information in estimation of breeding values for fine composition and technological properties of milk

Abstract: The aim of this study was to compare the common method of exploiting infrared spectral data in animal breeding; that is, estimating the breeding values for the traits predicted by infrared spectroscopy, and an alternative approach based on the direct use of spectral information (direct prediction, DP) to predict the estimated breeding values (EBV). Traits were pH, milk coagulation properties, contents of the main casein and whey protein fractions, cheese yield measured by micro-cheese making, lactoferrin, Ca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 11 publications
5
22
2
Order By: Relevance
“…The PLS factors are thus expected to give better prediction of the trait than the one with latent traits from PCA. However, with PLS, information about other milk composition traits not included in the calibration may not be retained in the factor scores, as also indicated by Dagnachew et al (2013b) and Bonfatti et al (2017). The expected better prediction of traits with PLS model was confirmed.…”
Section: Evaluation Of the Ip And Dp Approachessupporting
confidence: 59%
See 4 more Smart Citations
“…The PLS factors are thus expected to give better prediction of the trait than the one with latent traits from PCA. However, with PLS, information about other milk composition traits not included in the calibration may not be retained in the factor scores, as also indicated by Dagnachew et al (2013b) and Bonfatti et al (2017). The expected better prediction of traits with PLS model was confirmed.…”
Section: Evaluation Of the Ip And Dp Approachessupporting
confidence: 59%
“…It is also in contrast to the work of Dagnachew et al (2013b), who reported better prediction in accuracy of EBV for milk contents in goat by DP than IP approaches. Bonfatti et al (2017) also reported results that are mostly in contrast with the work of Dagnachew et al (2013b), who found high rank correlations (>0.94) between IP and DP predicted EBV of all traits investigated. Bonfatti et al (2017) reported <0.5 rank correlations between EBV predicted by IP and DP for most traits included in their study.…”
Section: Evaluation Of the Ip And Dp Approachescontrasting
confidence: 48%
See 3 more Smart Citations